Study on the Strength and Mechanism Analysis of Coarse Aggregate Reactive Powder Concrete - Xiuhong Hao; Haichuan Jia; Guangyao Ding; Xianxian Kong; Xianghe Meng (Buildings, 2025)
The demand for super-tall buildings and long-span bridges has driven concrete development toward higher strength and durability. Therefore, this study investigated the impact of composition of materials (aggregates, admixtures, and steel fibers) on the mechanical performance and economic feasibility of coarse aggregate reactive powder concrete (CA-RPC). The goal is to identify optimal combinations for both performance and cost. Scanning electron microscopy (SEM) and pore structure analysis were used to assess microstructural characteristics. The results demonstrated that replacing quartz sand with yellow sand as the fine aggregate in CA-RPC effectively reduced construction costs without compromising compressive strength. The use of basalt as the coarse aggregate led to higher mechanical strength compared to limestone. Incorporating 20% fly ash reduced the 7-day compressive strength, while the 28-day strength remained unaffected. The addition of 10% silica fume showed no obvious effect on the early strength but significantly improved the 28-day strength and workability of the concrete. Moreover, the incorporation of steel fibers improved the flexural strength and structural integrity of CA-RPC, shifting the failure mode from brittle fracture to a more ductile cracking behavior. SEM observations and pore structure analyses revealed that the admixtures altered the hydration products and pore distribution, thereby affecting the mechanical performance. This study provides valuable insights into the strength development and underlying mechanisms of CA-RPC, offering a theoretical basis for its practical application in bridge deck pavement and tunnels.